Nociceptin/orphanin FQ receptor expression in clinical pain disorders and functional effects in cultured neurons. Issue 9 (September 2016) - Anand, Praveen; Yiangou, Yiangos; Anand, Uma; Mukerji, Gaurav; Sinisi, Marco; Fox, Michael; McQuillan, Anthony; Quick, Tom; Korchev, Yuri E.; Hein, Peter
Abstract : Abstract: The nociceptin/orphanin FQ peptide receptor (NOP), activated by its endogenous peptide ligand nociceptin/orphanin FQ (N/OFQ), exerts several effects including modulation of pain signalling. We have examined, for the first time, the tissue distribution of the NOP receptor in clinical visceral and somatic pain disorders by immunohistochemistry and assessed functional effects of NOP and μ-opioid receptor activation in cultured human and rat dorsal root ganglion (DRG) neurons. Quantification of NOP-positive nerve fibres within the bladder suburothelium revealed a remarkable several-fold increase in detrusor overactivity ( P < 0.0001) and painful bladder syndrome patient specimens ( P = 0.0014) compared with controls. In postmortem control human DRG, 75% to 80% of small/medium neurons (⩽50 μm diameter) in the lumbar (somatic) and sacral (visceral) DRG were positive for NOP, and fewer large neurons; avulsion-injured cervical human DRG neurons showed similar numbers. NOP immunoreactivity was significantly decreased in injured peripheral nerves ( P = 0.0004), and also in painful neuromas ( P = 0.025). Calcium-imaging studies in cultured rat DRG neurons demonstrated dose-dependent inhibition of capsaicin responses in the presence of N/OFQ, with an IC50 of 8.6 pM. In cultured human DRG neurons, 32% inhibition of capsaicin responses was observed in the presence of 1 pM N/OFQ ( P < 0.001). The maximum inhibition of capsaicin responses was greater with N/OFQ than μ-opioid receptor agonist DAMGO. Our findings highlight the potential of NOP agonists, particularly in urinary bladder overactivity and pain syndromes. The regulation of NOP expression in visceral and somatic sensory neurons by target-derived neurotrophic factors deserves further study, and the efficacy of NOP selective agonists in clinical trials. Abstract : N/OFQ receptor (NOP) was found to be increased in bladder tissue from patients with painful bladder syndrome. Potent inhibition in cultured nociceptors indicates analgesic potential of NOP agonists.